Does conflict help or hurt cognitive control? Initial evidence for an inverted U-shape relationship between perceived task difficulty and conflict adaptation - van Steenbergen, Henk; Band, Guido P. H.; Hommel, Bernhard (Frontiers in Psychology, 2015)
Sequential modulation of congruency effects in conflict tasks indicates that cognitive control quickly adapts to changing task demands. We investigated in four experiments how this behavioral congruency-sequence effect relates to different levels of perceived task difficulty in a flanker and a Stroop task. In addition, online measures of pupil diameter were used as a physiological index of effort mobilization. Consistent with motivational accounts predicting that increased levels of perceived task difficulty will increase effort mobilization only up to a certain limit, reliable dynamic conflict-driven adjustment in cognitive control was only observed when task difficulty was relatively low. Instead, tasks tentatively associated with high levels of difficulty showed no or reversed conflict adaptation. Although the effects could not be linked consistently to effects in self-reported task difficulty in all experiments, regression analyses showed associations between perceived task difficulty and conflict adaptation in some of the experiments, which provides some initial evidence for an inverted U-shape relationship between perceived difficulty and adaptations in cognitive control. Furthermore, high levels of task difficulty were associated with a conflict-driven reduction in pupil dilation, suggesting that pupil dilation can be used as a physiological marker of mental overload. Our findings underscore the importance of developing models that are grounded in motivational accounts of cognitive control.